Comparative Analysis of the Color Stability of Different Ceramic Materials after Exposure to Staining Solutions - Siddharam M. Patil; Bharani K. Bhattu; Hend Mohamed Elsayed; Naina Pattnaik; Ruchi Patel; Manish Kumar; Mahesh Ghadage; Dipooja Patil (Journal of Pharmacy and Bioallied Sciences)
Background: Color stability is a critical factor influencing the aesthetic success of ceramic materials in dentistry. This study evaluates and compares the color stability of three commonly used ceramic materials—lithium disilicate, zirconia, and feldspathic porcelain—after exposure to staining solutions to determine their clinical performance under challenging oral conditions. Materials and Methods: A total of 60 ceramic specimens (20 from each material group) were fabricated and polished to standardized dimensions. Each group was subdivided into four subgroups (n = 5) based on the staining solutions: coffee, red wine, cola, and distilled water (control). The specimens were immersed in their respective solutions for 7 days at 37°C. Color measurements were performed using a spectrophotometer at baseline and after immersion, and color change (ΔE) values were calculated using the CIELAB color system. Statistical analysis was conducted using ANOVA and post hoc tests (P < 0.05). Results: The mean ΔE values for lithium disilicate were 4.5 ± 0.8, 5.2 ± 1.0, 3.6 ± 0.6, and 0.9 ± 0.2 for coffee, red wine, cola, and control, respectively. Zirconia exhibited ΔE values of 3.2 ± 0.5, 4.1 ± 0.7, 2.8 ± 0.4, and 0.8 ± 0.1, while feldspathic porcelain showed the highest ΔE values of 6.7 ± 1.2, 7.5 ± 1.4, 5.3 ± 0.9, and 1.0 ± 0.2 for the respective solutions. Statistically significant differences were observed between the materials and staining solutions (P < 0.05), with feldspathic porcelain being the most affected and zirconia the least. Conclusion: The study revealed significant differences in the color stability of ceramic materials after exposure to staining solutions. Zirconia exhibited superior resistance to staining, followed by lithium disilicate and feldspathic porcelain.